ANALISIS DAN PERANCANGAN JARINGAN HOTSPOT SERVER BERBASIS MIKROTIK DENGAN METODE NETWORK DEVELOPMENT LIFE CYCLE (NDLC) DI GOODDANK.INC KOTA MALANG - Muhammad Iqbal Tawakkal Dewanto; Sigit Kusmaryanto; Ali Mustofa (Jurnal Mahasiswa TEUB, 2020)
Abstract—- Hotspot is a system for providing authentication features to users who will use the internet network. So to be able to access the internet network, the client must enter a user name and password on the login page provided. To turn Wi-Fi networks into network hotspots, Mikrotik is installed using Virtual Box. While setting Mikrotik in Grapichal User Interface (GUI) mode is done with. To overcome the blank point because it reduces the number of access points needed by the access point with the initial steps of calculating the link budget. The next step is simulation with the Ekahau Site Survey to analyze and solve blank spot problems. The final step is to survey the site with Netspot to prove the simulation results. The parameter analyzed is the signal strength in units of dBm. Index Terms—Mikrotik, Hotspot, COST-231 Multi Wall, Ekahau Site Survey, NetSpot